Preparation of HgI2 Films Using Solvent Evaporation - Gaafar M. Mousa (Engineering and Technology Journal, 2009)
A deposited layer of HgI2 has been prepared by using the solution technique. This technique takes a long time about (10 days) to get a film. The deposition time in this work reduced to (24 hours). The film consist of 2.25 mm thick layer of HgI2.The band gap energy and type of optical transition were determined from transmission spectra, and an optical band gap of Eg =2.12 eV for direct transition was estimated. x-ray diffraction of HgI2 to film shows a preferential orientation of peaks (101) and (102).